دعوت وتفہیم دین کے قرآنی اصول: ایک تجزیاتی مطالعہ: The Qurʻānic Principles of Daᶜwah and Understanding Religion: An Analytical Study (Al-Qamar, 2020)
The holy Quran discusses principles and it often does so with brevity. And the details and explanation of these principles is expounded by Aḥādith. But the Holy Quran explains the principles where necessary. So where the Holy Quran discusses different topics & matter, It also elaborates the principles of  Daᶜwat-e-Dīn. By following the principles, set by the holy Quran, the Holy prophet P.B.U.H. preached Daᶜwat-e-Dīn. The effective method Preach Daᶜwat-e-Dīn adopted by the Holy Prophet  is the only way to be followed in order to convey the principles of  Quran effectively. In this article, we have discussed the principles of  Daᶜwat-e-Dīn described by the Holy Quran and how the Holy Prophet has implemented these principles in connection with Daᶜwat-e-Dīn.
Keywords: Daᶜwat-e-Dīn; Qurʻānic Principles; Method of Preaching; Sīrah